ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY RISK IN THE 76MM SHOOTING PROCESS USING HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) METHODS - Dwi Prasetyo (AGUSPATI Research Institute, 2023)
The Meriam Otomelara 76 mm is a strategic weapon of the KRI which functions as an anti-surface and anti-aircraft weapon owned by the Ahmad Yani or Van Speijk class of KRI. The high usage of the 76mm gun during exercises, as well as the age of the KRI and its weapon system, can affect the success of training tasks and create the risk of work accidents that can harm personnel and material. To anticipate work accidents in the KRI and base environment, the Indonesian Navy has launched the